2003
DOI: 10.1002/ar.a.10001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of knee‐joint cartilage morphology with muscle cross‐sectional areas vs. anthropometric variables

Abstract: We tested the hypothesis that muscle cross-sectional areas (MCSAs) are more highly (and independently) correlated with cartilage morphology than are body height and weight, and that the physiological reduction of cartilage thickness with aging is associated with a proportional, age-dependent decrease in MCSAs. In 59 asymptomatic individuals (23-75 years old), morphological parameters of the knee cartilages (volume, thickness, and bonecartilage interface area), and MCSAs were determined from magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 40 publications
4
64
2
1
Order By: Relevance
“…Moreover, increased mass of muscles was reported to be strongly associated with the volume of medial tibia cartilage. Hudelmaier et al also demonstrated that a positive correlation is present between mass of muscles and volume of knee cartilage (23). Therefore, muscle strengthening exercises are of crucial significance in the treatment of knee OA (22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased mass of muscles was reported to be strongly associated with the volume of medial tibia cartilage. Hudelmaier et al also demonstrated that a positive correlation is present between mass of muscles and volume of knee cartilage (23). Therefore, muscle strengthening exercises are of crucial significance in the treatment of knee OA (22).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the correlation with the knee angle was stronger for the tibial than for the femoral cartilage plates 139). Although the differences exceeded the precision errors of the measurements substantially, T-scores (deviation from young, healthy volunteers of the same sex divided by the SD of values in these volunteers) were only moderate, owing to the relatively large intersubject variability in healthy volunteers (82,83,140,141). It was shown in osteotomy and TKA patients that T-scores were substantially increased when cartilage volume (VC) was normalized to the total area of subchondral bone (VCtAB) and that the normalization was more effective than normalization to body weight or height (89).…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 95%
“…For example, increased physical activity was positively associated with increased knee articular cartilage volume in a cross-sectional study (Jones et al, 2000) and a longitudinal study (Jones et al, 2003) of healthy children, implying that loading has a positive effect on the articular cartilage of healthy population. Similarly, larger muscle cross-sectional areas were positively associated with increased knee articular cartilage volumes in healthy subjects (Hudelmaier et al, 2003). More specifically mechanical loads during walking have been shown to have a positive influence on healthy cartilage .…”
Section: Introductionmentioning
confidence: 97%